Mediatization of Hadith and the Spirit of Da’wah Moderation in Infographic Content of Online Media - Mundzir, Muhammad (Journal for the study of religions and ideologies, 2023)
One of the movements that online preachers continue to campaign for is the mediatization of hadith. This is due to the transformation of da’wah media from conventional to digital. Mediatization of hadith, one of which is displayed in infographics such as Republika.co.id, is an online media that has also colored the new face of hadith reception on Indonesian social media. This paper aims to reveal da’wah’s ideological bias or character in the mediatization of hadith. This article falls into the category of qualitative research. Data is collected or sourced from the online media website Republika.co.id, infographic channels, and focus on the religion column. It was revealed that there was a shift in the process of narrating religious texts caused by technological developments, thus presenting a new challenge for the preachers that the habit of the Indonesian people today is to love something instant. This article also finds the infographic content of hadith presented by Republika to be one of the portraits of the mediatization of hadith that was previously written in classical books. Now the infographic content has undergone several changes, including: there is a development of meaning, development of translation, limitation of meaning, and disharmony between the title of the content with the hadith delivered. The infographic content presented by Republika.co.id also has a moderating dimension, namely seeing empirical reality and not justifying understanding to one group.